Novel stereo DIC characterisation of microneedle and hypodermic needle insertion - McNamee, Megan; Pritchard, Thomas; Mitchell, Jacob; Bolton, Chris; Roberts, Kerry; Guy, Owen; Ashraf, Huma; Arora, Hari (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMicroneedles are minimally invasive devices, designed for pain-free drug delivery. Until now, the degree of strain exerted on the skin during microneedle insertion, in comparison to gold standard hypodermic needles, has not been quantified.MethodsThis paper presents experimental results from a novel digital image correlation setup to quantify maximum normal strain exerted on a skin-mimicking membrane by hollow silicon microneedles and 25-gauge stainless steel hypodermic needles through contact, deformation, rupture, and device insertion.ResultsFindings here have shown 1 × 5 hollow silicon microneedle arrays exert significantly lower maximum normal strain compared to 25-gauge hypodermic needles. There is an average of 75% decrease in the maximum normal strain experienced by the membrane when using microneedle devices in comparison to that of the 25-gauge hypodermic needles. This quantification of strain has been discretised to each individual needle in the microneedle device, allowing for informed design choices for future device iterations.DiscussionThese findings suggest the hollow microneedle devices to be a gentler alternative for transdermal applications, potentially improving patient comfort and reducing tissue trauma when compared to the gold standard, traditional 25-gauge hypodermic needle.